2006
DOI: 10.1007/s10535-006-0044-y
|View full text |Cite
|
Sign up to set email alerts
|

Histological characterization of in vitro adventitious organogenesis in Citrus sinensis

Abstract: The adventitious bud development was induced in epicotyl segments of Valencia sweet orange (Citrus sinensis L. Osbeck). Seeds were cultured in vitro for three weeks in the dark, followed by one week at a 16-h photoperiod. Epicotyl segments were cultured horizontally for the induction of organogenesis in Murashige and Tucker (1969, MT) culture medium supplemented with 1.0 mg dm -3 benzylaminopurine. Samples were observed by light and scanning electron microscopy from day zero to day 25, when buds were well grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 11 publications
1
5
0
4
Order By: Relevance
“…This result can be explained with the presence of predetermined cells which first dedifferentiate themselves, subsequently form new meristematic centres, and finally differentiate again producing new organs [34][35][36][37][38][39]. This process, due to cell totipotency, has been observed in several species [30,[40][41][42][43][44][45][46][47] and is very efficient for regeneration. Our results showed that AFLP is a very sensitive and reliable molecular marker technique for revealing specific genomic alterations induced by tissue culture and for identifying slightly different genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…This result can be explained with the presence of predetermined cells which first dedifferentiate themselves, subsequently form new meristematic centres, and finally differentiate again producing new organs [34][35][36][37][38][39]. This process, due to cell totipotency, has been observed in several species [30,[40][41][42][43][44][45][46][47] and is very efficient for regeneration. Our results showed that AFLP is a very sensitive and reliable molecular marker technique for revealing specific genomic alterations induced by tissue culture and for identifying slightly different genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to this research, explants with more differentiated tissues than meristems like scutellum of embryo were used to induce direct somatic embryogenesis pathway in seven cereal species (Eudes et al 2003). It has been proven that globular somatic embryos originate from the epidermal and subepidermal cells of the explant (Laparra et al 1997;Quiroz-Figueroa et al 2002;Petitprez et al 2005), while shoot organogenesis derives from meristematic shoot initials at different anatomical layers (Zhang et al 1998;de Almeida et al 2006;Veit 2006). Co-induction of direct shoot organogenesis and direct somatic embryogenesis pathways on different parts of a single explant, in response to the same hormonal cues, clearly shows the vital effect of the site in response to hormone.…”
Section: Discussionmentioning
confidence: 99%
“…As also mentioned by Almeida, Mourao Filho, Mendes, & Rodríguez (2006), a direct regeneration pathway may be used for transformation purposes as a means to avoid the formation of chimeric plants and genetic variability, which can occur through regeneration from callus. This protocol may be a useful tool for micropropagation of the species as well as for the application of genetic transformation techniques, as it enables us to determine specific regions in the foliar explant where initiation of meristemoids will take place, and therefore to determine which cells should be the object of genetic transformation.…”
Section: Discussionmentioning
confidence: 99%